Revolutionizing Islamic Religious Education in the Age of Society 5.0 through Curriculum Innovation at Merdeka Learning Merdeka Campus (MBKM) - Sofa, Ainur Rofiq; Muttaqin, Ahmad Izza; Tohet, Moch; Mundir, Mundir; Machfudi, Moch. Imam; Mukniah, Mukniah (IJIE International Journal of Islamic Education, 2023)
The existing Islamic religious education curriculum shows a clear separation between subjects like Al-Qur'an, Hadith, Fiqh, Aqidah, and the history of Islamic culture. Full integration of these elements is lacking, but it has the potential to improve students' religious experiences by providing comprehensive support for worship. Madrasah institutions face challenges related to ownership, environment, and teachers adapting to technological advancements in the current era. This study aims to explore how PAI (Islamic Religious Education) teachers implement innovative approaches in madrasahs. Employing a qualitative research design with a literature review methodology, information was gathered from various regulations, books, and magazines. We opted for a qualitative approach to explore innovative curriculum changes that can improve the quality of millennial-era madrasahs with Islamic characteristics. The literature review exposed a predominant focus on subject-centric designs influenced by teachers and infrastructure in constructing Islamic religious education curricula in madrasahs. In response, a proposed ideal model emphasizes an integrated learning approach tailored for the millennium era. This model strives to enhance Islamic language skills through integration. The study concludes by underlining key themes: innovation, curriculum development, Islamic religious education, madrasah, and the era of Society 5.0.